Nonhepatic Cell Lines HeLa and 293 Support Efficient Replication of the Hepatitis C Virus Genotype 2a Subgenomic Replicon - Kato, Takanobu (American Society for Microbiology, 2005)
The hepatitis C virus (HCV) genotype 2a subgenomic replicon can replicate in two human non-hepatocyte-derived cell lines, HeLa and 293, with in vitro-transcribed replicon RNA. Sequencing analysis revealed that mutations in HCV-derived regions were not essential for replication in these cells, as some clones displayed no mutations.